Pengarsipan Dokumen Perkara Pada Pengadilan Tata Usaha Negara Banjarmasin - Aldo Yanuarto; Alvianur Alvianur; Aji Santoso; Muhammad Syahbintang Maesa Putra; Dody Wahyudi; Novita Ayu Fitri Wulandari; Fayzah Nazmah; Rani Komalasari; Muhammad Amin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The archiving of case documents that have obtained permanent legal force (inkracht) at the State Administrative Court (PTUN) of Banjarmasin is a crucial aspect of judicial administration, serving to maintain the accuracy of legal documentation while supporting transparency and accountability within the judicial system. This process includes the recording, storage, and disposal of documents in accordance with applicable regulations, as stipulated by the Supreme Court and national archival regulations. From the perspective of Public Administration Theory, archival management must be conducted systematically and based on regulations to enhance the efficiency and effectiveness of judicial services. Meanwhile, according to the Theory of Judicial Transparency and Accountability, information openness in archival management plays a significant role in building public trust in the judiciary. Although PTUN Banjarmasin has implemented an archiving system that complies with established standards, challenges in the digitalization of archives remain an obstacle, particularly in terms of technology optimization and human resource readiness. Therefore, strengthening digital-based archival systems and enhancing judicial administrative capacity are strategic measures to improve document management efficiency, reduce the risk of loss or damage to physical archives, and reinforce judicial transparency and accountability.